Using Proanthocyanidin as a Root Dentin Conditioner for GIC Restorations. (September 2021) - Cai, J.; Burrow, M.F.; Manton, D.J.; Palamara, J.E.A.
Glass ionomer cements (GICs) are considered the material of choice for restoration of root carious lesions (RCLs). When bonding to demineralized dentin, the collapse of dentinal collagen during restorative treatment may pose challenges. Considering its acidic nature and collagen biomodification effects, proanthocyanidin (PAC) could be potentially used as a dentin conditioner to remove the smear layer while simultaneously acting to biomodify the dentinal collagen involved in the bonding interface. In this study, 6.5% w/v PAC was used as a conditioner for sound (SD) and laboratory demineralized (DD) root dentin before bonding to resin-modified GIC (FII), casein phosphopeptide–amorphous calcium phosphate (CPP-ACP)–modified GIC (FVII), or a high-viscosity GIC (FIX). Root dentin conditioned with deionized distilled water (DDW) or polyacrylic acid (PAA) served as controls. Results indicated FII showed higher shear bond strength (SBS) on SD than the other 2 GICs, especially in PAA-conditioned samples; FIX showed significantly higher SBS than FII and FVII on PAA- or PAC-conditioned DD. In each category of GIC, PAA and PAC did not have a significant influence on SBS in most cases compared to DDW except for a significant decrease in PAC-conditioned SD bonded to FII and a significant increase in PAA-conditioned DD bonded to FIX. The bonding interface between GIC and SD was generally more resistant to the acid-base challenge than DD. Although the alterations in failure modes indicated a compromised interfacial interaction between GICs and PAC-treated root dentin, biomodification effects of PAC on dentin were observed from Raman microspectroscopy analysis in terms of the changes in mineral-to-matrix ratio and hydroxyproline-to-proline ratio of dentin adjacent to the bonding interface, especially of DD. Results from this study also indicated the possibility of using in situ characterization such as Raman microspectroscopy as a complementary approach to SBS test to investigate the integrity of the bonding interface.